The Relationship between Achievement Motivation and Cheating Behavior of students of SMA X Makassar - Airai Putri, Andi Indira; Puspita Dewi, Eva Meizara; Halimah, Andi (Polteknik Ilmu Pemasyarakatan, 2025)
This study aims to determine the relationship between achievement motivation and cheating behavior of SMA X Makassar students. This study uses a quantitative approach using an achievement scale and a cheating scale. The population in this study is students of grades X and XI of SMA X Makassar with a sampling technique using a simple random sampling method. The research involved 249 students of SMA X Makassar. The r value of -0.450 (p=0.000) in the results of this study showed that there was a negative and significant relationship between achievement motivation and cheating behavior of SMA X Makassar students. The higher the achievement motivation, the lower the student's cheating behavior. On the other hand, the lower the motivation for achievement, the higher the cheating behavior possessed by students. The findings of this study have implications for the development of knowledge related to achievement motivation and cheating behavior, as well as providing guidance for students and teachers to increase their achievement motivation in order to reduce and avoid cheating behavior at school.